1990
DOI: 10.1016/s0022-5347(17)39562-9
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in the Treatment of Chyluria in Taiwan

Abstract: From 1967 through 1986, 55 patients with chyluria were treated by renal pelvic instillation of 10 ml. 0.5% silver nitrate solution and surgical disconnection of the renal pedicle lymphatics was done in 9 (16.3%) due to persistent chyluria after instillation therapy. Among these 46 renal pelvic instillation patients and 9 operated patients followed for 2 years chyluria recurred in 11 (22.7%) and 5 (55.5%), respectively. Renal pelvic instillation is a safe and effective method to treat chyluria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 13 publications
1
36
1
Order By: Relevance
“…Yamuchi [5] used 1-2% solution; Okamoto and Ohi [4] used 10 ml, 0.1-0.5% solution 2-3 times/week with a maximum up to 10 instillations, with 59.4% response rate. Tan et al [6] used 10 ml 0.5% solution, maximum up to 3 instillations with 80% response rate and 22.7% recurrence rate in 2-21 years of follow-up. Apparently, there is lack of consensus among urologists regarding the concentration and number of instillations of silver nitrate solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamuchi [5] used 1-2% solution; Okamoto and Ohi [4] used 10 ml, 0.1-0.5% solution 2-3 times/week with a maximum up to 10 instillations, with 59.4% response rate. Tan et al [6] used 10 ml 0.5% solution, maximum up to 3 instillations with 80% response rate and 22.7% recurrence rate in 2-21 years of follow-up. Apparently, there is lack of consensus among urologists regarding the concentration and number of instillations of silver nitrate solution.…”
Section: Discussionmentioning
confidence: 99%
“…Pyelolymphatic disconnection (surgical disconnection of lymphatics at the renal hilum) with or without renal decapsulation, though reported to be effective with a low recurrence rate, is a major surgical procedure [7,8]. Punekar et al [9] reported good results with this operation and recommend it as first-line treatment, however other workers recommend surgery only after an attempt with silver nitrate instillation sclerotherapy has failed [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatments, including bed rest, more water, and a fat-restricted, high-protein diet are recommended for those with mild chyluria or in poor condition without tolerance for surgery. Instillation of the renal pelvis with silver nitrate or povidone iodine has been used, [6][7][8] and because of the drawbacks of recurrence and repeated instillation and pain, this procedure is now less adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde injection of sclerotherapeutic agents (5% povidone iodine or 0.5% silver nitrate) into the ureter and pelvi-calyceal system of the affected side have been found to be palliative in moderate cases of chyluria. The treatment regimen consists of 5-10 ml of sclerosants instillation weekly for about 4 weeks or three times daily (TDS) for 2-3 days [58] . Such regimens have been reported to be 60-70% successful in mild to moderate cases of chyluria [57] .…”
Section: Treatmentmentioning
confidence: 99%